Male police officers’ law enforcement preferences in cases of intimate partner violence versus non-intimate interpersonal violence: do sexist attitudes and empathy matter? - Gracia, Enrique (Criminal justice and behavior, 2014)
This article explores male police officers' law enforcement preferences across different scenarios of interpersonal violence, involving intimate (partner violence against women) and non-intimate relationships (between- and within-gender). The influence of police officers? sexist attitudes and empathy on their law enforcement preferences was also analyzed within and across these scenarios. The sample consisted of 308 male police officers. Results showed that police officers prefer a stronger and unconditional law enforcement approach in cases of violence against women, both in intimate and non-intimate relationships. Benevolent sexism was linked to a preference for a more conditional law enforcement across interpersonal violence scenarios. The type of interpersonal violence scenario also conditioned the influence of hostile sexism and empathy on police preferences. Implications for training and selection of police officers are discussed.